Quality of carrageenan extracted from Eucheuma cottonii cultivated at three different locations in Lampung. Issue 1 (November 2021) - Subaryono,; Utomo, B S B; Basmal, J
Abstract: This study aims to compare the quality of carrageenan extracted from Eucheuma cottonii harvested from three different seaweed cultivation locations at Ketapang, South Lampung. The three locations selected were Ruguk, Legundi and Tri Dharma Yoga Villages. Some important quality parameters were observed to compare the quality of carrageenan covering yield, viscosity and gel strength, in addition, the other three supporting parameters were moisture, ash, and acid insoluble ash content. Results showed that the viscosity of carrageenan from the three locations ranged from 736.67-936.67 cP and gel strength 487.77-538.22 g/cm 2, while moisture, ash and acid insoluble ash content were 12.09-13.94%, 16.28-17.13%, and 0.27-0.33%, respectively. It was concluded that the quality of carrageenan from Legundi Village was the best compared to those from the two other villages.